On comparing the resurrection appearances with apparitions - Siniscalchi, Glenn B. (Pacifica, 2014)
After building a historical case for the post-mortem appearances of Jesus, I discuss the current landscape of apparitions research within the field of parapsychology. A balanced comparison of these two visual phenomena indicates that there are many more differences than similarities that might obtain between them. Because the resurrection appearances were seen as unique irruptions of the divine in human history, apparitions cannot be used as the primary basis for understanding the nature of the appearances. By interacting with Dale Allison's references to apparitions and, by extension, the historical credibility of the resurrection of Jesus, the argument of this article seeks to reinstate the uniqueness of the resurrection appearances.